Program Penguatan Akhlak Islami melalui Kegiatan Sosial dan Dakwah Komunitas - Siti Istianah; Solikhin (Jurnal Ragam Pengabdian, 2025)
This community service program aims to strengthen Islamic morality among youth through social activities and community-based da’wah organized by the Youth of Al-Ikhlas Mosque (RDM). The implementation method consisted of preparation, execution of moral studies and da’wah activities, mentoring of social practices, and program evaluation. The results indicated a significant improvement in understanding Islamic moral values, increasing from 60% in the pre-test to 85% in the post-test. Furthermore, active involvement of the youth in social activities such as charity events, assistance for the needy, and environmental care initiatives facilitated the internalization of Islamic values in their daily lives. The program not only focused on spiritual development but also emphasized community empowerment and organizational capacity building of RDM. Thus, the community service program conducted by RDM Al-Ikhlas has proven to be an effective model in shaping a morally upright and socially responsible young generation, which can be replicated in other mosque-based youth communities.